Dignosis Of Cutaneous And Sub Cutaneous Pathological Lesions In Dogs Through Ultrasound Guided Biopsy - Jain, Pankaj; Shahi, Apra; Swamy, Madhu (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A total of 127 dogs were scanned ultrasonographically at Teaching Veterinary Clinical Complex, Jabalpur out of which 24 dogs underwent ultrasound guided tissue core biopsy (TCB) or fine needle aspiration cytology (FNAC) to diagnose the cutaneous and sub cutaneous lesions. Only five dogs were found positive to have pathological lesions after performing cytological and histopathological examination of collected samples. Out of these five cases, one was having haematoma while inguinal lymph node of second dog revealed chronic reactive lymphoid hyperplasia. Enlarged popliteal lymph node in third dog revealed lymphoma. Fourth dog was found to be afflicted with myositis while fibroma was confirmed in fifth dog. Affected animals were treated successfully with surgical and medicinal intervention. It was concluded that ultrasound guided TCB and FNAC were effective tools in diagnosing cutaneous and subcutaneous lesions without having any negative consequences.
Keywords: Core biopsy; dogs; fine needle aspiration; ultrasound